Samsonova legitimita : příběh biblického hrdiny a jeho místo v knize Soudců - Churaňová, Barbora (Religio, 2024)
The purpose of this article is to present a new perspective on the biblical judge Samson. The author draws on previous work on this character and works with the concept of Samson‘s liminal nature, which allows him to mediate between two cultures, Israeli and Philistine. This quality of his is seen as essential. It is because of it that he can be a judge, and not in spite of it, as has often been perceived. The paper then develops this approach further and adds a view of Samson‘s legitimating role within the period of the judges. The article employs a structuralist approach and Samson is thus placed in opposition between the Israelite and Philistine cultures, which also have a geographical expression in the form of the opposition between the city and the desert. Samson‘s mediating role and liminal status is connected to Samson‘s trickster nature, which better enables his movement between cultures. This movement is then central to the entire narrative of the Book of Judges, in the context of which Samson‘s story should be read. Comparing his story with the stories of the other Judges reveals that Samson is both a kind of culmination of this time and a conclusion to it. Because of his liminal nature, he is able to embody the contradictions in Israelite culture and carry them over into the following age of kings.